Komposisi Serat Ransum Komplit Berbasis Daun Jati Putih (Gmelina arborea) Pada Lama Peyimpanan Yang Berbeda - Sadi, Ristasari (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
A complete ration contains full necessary nutritional substances for the livestock at a certainphysiological level. The ration is made as a sole source of nutrients, excluding water for basic livingneeds and production. This study aims to analyze the fiber composition of white teak leaf-basedcomplete ration at different storage periods. This study employed a Completely Randomized Design(CRD) with 3 treatments and 3 replicates encompassing T1 (0-week storage period), T2 (4-weekstorage period), and T3 (8-week storage period). Research result indicated that different periods ofstorage period had a significant effect (P<0.05) on complete ration NDF, ADF, hemicellulose,cellulose and lignin. However, no significant effect was identified from cellulose content. Inconclusion, an 8-week storage period did not significantly affect the fiber composition of the whiteteakleaf-basedcompleteration.